Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics

First principles calculations of thermal, equations of state and thermodynamical properties of MgH2 at finite temperatures - Kelkar, Tuhina; Kanhere, Dilip G.; Pal, Sourav (Computational Materials Science, 2008)
We present the first principles calculations of the thermodynamical properties of magnesium hydride (MgH2) over a temperature range of 0-1000 K. The phonon dispersions are determined within the density functional framework and are used to calculate the free energy of MgH2 within the quasiharmonic approximation (QHA) at each cell volume and temperature T. Using the free energies the thermal equation of state (EOS) is derived at several temperatures. From the thermal EOS structural parameters such as the equilibrium bell volume (V-0) and elastic properties, namely, bulk modulus (K-0) and its pressure derivative (K-0(')) are computed. The free energies are also used to calculate various thermodynamical properties within QHA. These include internal energy E, entropy S, specific heat capacity at constant pressure C-P, thermal pressure P-thermal(V,T) and volume thermal expansion Delta V/V (%). The good agreement of calculated values of S and Cp with experimental data exhibits that QHA can be used as a tool for calculating the thermodynamical properties of MgH2 over a wide temperature range. P-thermal(V,T) increases strongly with T at all the volumes but it is a slowly varying function of volume for T = 298-500 K. According to Karki [B.B. Karki, Am. Miner. 85 (2000) 1447] such volume based variations can be neglected and so it is possible to estimate the thermal EOS only with the knowledge of the measured P-thermal(V,T) versus temperature at ambient pressure and isothermal compression data at ambient temperature. Temperature dependence of Delta V/V(%) shows that V-0 increased with increase in temperature. However, the percentage decrease in K-0 superseded this percentage increase in V-0 even at temperatures moderately higher than 298 K. Therefore, we suggest application of temperature (T > 298 K) as an approach to enhance the hydrogen storage capacity of MgH2 because of its better compressibility at these temperatures. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: equation of state; Hydrogen storage; lattice dynamics; magnesium hydride; Thermodynamic properties

Model study of effect of M = Li+, Na+, Be2+, Mg2+, and Al3+ ion decoration on hydrogen adsorption of metal-organic framework-5 - Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2010)
The effect of light metal ion decoration of the organic linker in metal organic framework MOF 5 on its hydrogen adsorption with respect to its hydrogen binding energy (Delta B E) and gravimetric storage capacity is examined theoretically by employing models of the form MC6H6 nH(2) where M = Li+ Na+ Be2+ Mg2+ and Al3+ A systematic investigation of the suitability of DFT functionals for studying such systems is also carried out Our results show that the interaction energy (Delta E) of the metal ion M with the benzene ring Delta B E and charge transfer (Q(trans)) from the metal to benzene ring exhibit the same increasing order Na+ < Li+ < Mg2+ < Be2+ < Al3+ Organic hnker decoration with the above metal ions strengthened H-2 MOF 5 interactions relative to its pure state However amongst these ions only Mg2+ ion resulted in Delta B E magnitudes that were optimal for allowing room temperature hydrogen storage applications of MOF 5 A much higher gravimetric storage capacity (6 15 wt % H-2) is also predicted for Mg2+ decorated MOF 5 as compared to both pure MOF 5 and Li+ decorated MOF (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: Binding energy; Hydrogen adsorption; Hydrogen storage; Metal organic frameworks

Ab initio and periodic DFT investigation of hydrogen storage on light metal-decorated MOF-5 - Dixit, Mudit; Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2011)
The effect of light metal (M = Li, Be, Mg, and Al) decoration on the stability of metal organic framework MOF-5 and its hydrogen adsorption is investigated by ab initio and periodic density functional theory (DFT) calculations by employing models of the form BDC:M-2:nH(2) and MOF-5:M-2:nH(2), where BDC stands for the benzenedicarboxylate organic linker and MOF-5 represents the primitive unit cell. The suitability of the periodic DFT method employing the GGA-PBE functional is tested against MP2/6-311 + G* and MP2/cc-pVTZ molecular calculations. A correlation between the charge transfer and interaction energies is revealed. The metal-MOF-5 interactions are analyzed using the frontier molecular orbital approach. Difference charge density plots show that H-2 molecules get polarized due to the charge generated on the metal atom adsorbed over the BDC linker, resulting in electrostatic guest-host interactions. Our solid state results show that amongst the four metal atoms, Mg and Be decoration does not stabilize the MOF-5 to any significant extent. Li and Al decoration strengthened the H-2-MOE-5 interactions relative to the pure MOF-5 exhibited by the enhanced binding energies. The hydrogen binding energies for the Li- and Al-decorated MOF-5 were found to be sensible for allowing reversible hydrogen storage at ambient temperatures. A high hydrogen uptake of 4.3 wt.% and 3.9 wt.% is also predicted for the Li- and Al-decorated MOF-5, respectively. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ab initio calculations; Density functional theory; Hydrogen binding energies; Hydrogen storage; Metal-Pi-Arene interactions

Structural and gas adsorption study of a two-dimensional copper-tetrazole based metal-organic framework - Pachfule, Pradip; Banerjee, Rahul (Current Science, 2011)
A new two-dimensional (2D) metal organic framework, Cu-1(4-TBA)(1)(DMBP)(1).DMF (Cu-TBA-3), has been synthesized under solvothermal condition from transition metal cation Cu(II), predesigned ligand 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and coligand 4,4'-dimethy1-2,2'-bipyridine (DMBP). The structure has been determined by single crystal X-ray crystallography which shows layered 2D structure with square shaped one-dimensional channels. Cu-TBA-3 shows 0.69 wt% H-2 (at 77 K, 1 atm) and 1.65 mmol/g CO2 (at 298 K, 1 atm) uptake.
Keywords: CO2 capture; Hydrogen storage; metal-organic frameworks; microporous materials

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Control of porosity by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template for porous carbon synthesis - Pachfule, Pradip; Biswal, Bishnu P.; Banerjee, Rahul (Chemistry-A European Journal, 2012)
Herein, by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template, we report the synthesis, morphology, and gas adsorption properties of porous carbon synthesized by a nanocasting method at 1000 degrees C, in which furfuryl alcohol (FA) was used as a carbon source. By using IRZIFs with variable porosity as templates, we could achieve control over the carbon porosity and H-2 and CO2 uptake. The resultant microporous carbon C-70, synthesized by using ZIF-70 as the template, is the most porous (Brunauer-Emmett-Teller (BET) surface area 1510 m(2)g(-1)). Carbon C-68, synthesized by using ZIF-68, has moderate porosity (BET surface area 1311 m(2)g(-1)), and C-69, synthesized by using ZIF-69, has the lowest porosity in this series (BET surface area 1171 m(2)g(-1)). The porous carbons C-70, C-68, and C-69, which have graphitic texture, have promising H2 uptake capacities of 2.37, 2.15, and 1.96 wt%, respectively, at 77 K and 1 atm. Additionally, C-70, C-68, and C-69 show CO2 uptake capacities of 5.45, 4.98, and 4.54 mmolg(-1), respectively, at 273 K and 1 atm. The gas uptake trends shown by C-70, C-68, and C-69 clearly indicate the dependence of carbon porosity on the host template. Moreover, the as-synthesized carbons C-70, C-68, and C-69 show variable conductivity.
Keywords: Carbon; Hydrogen storage; metal-organic frameworks; microporous materials; zinc

Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction

Functionalized metal organic frameworks (MOFs) for reversible gas storage and sequestration applications - Banerjee, Rahul (Journal of the Indian Chemical Society, 2012)
The decreasing amount of fossil fuels and increasing threat of global warming from the pollutants have driven the search for clean energy source. Energy sources from fossil fuels still remain in the forefront despite being a major source of increased CO2 content in the atmosphere. Metal Organic Frameworks (MOFs) have emerged as promising materials for hydrogen storage and CO2 sequestration. Several factors influencing the hydrogen uptake of porous MOFs such as surface area, catenation, ligand functionalization, doping with alkali metals and unsaturated metal centers have been extensively studied. Similarly, well defined periodicity and tunable pore sizes along with less basic amino-functionalized MOFs enables them favorable for fast and reversible CO2 gas adsorption at low partial pressure and room temperature. In this review we present diverse aspects of metal organic frameworks like fluorination, amino functionalization for high hydrogen storage and CO2 sequestration capabilities.
Keywords: carbon capture; CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Hydrogen storage in clathrate hydrates: Current state of the art and future directions - Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Applied Energy, 2014)
Hydrogen is looked upon as the next generation clean energy carrier, search for an efficient material and method for storing hydrogen has been pursued relentlessly. Improving hydrogen storage capacity to meet DOE targets has been challenging and research efforts are continuously put forth to achieve the set targets and to make hydrogen storage a commercially realizable process. This review comprehensively summarizes the state of the art experimental work conducted on the storage of hydrogen as hydrogen clathrates both at the molecular level and macroscopic level. It identifies future directions and challenges for this exciting area of research. Hydrogen storage capacities of different clathrate structures - sI, sII, sH, sVI and semi clathrates have been compiled and presented. In addition, promising new approaches for increasing hydrogen storage capacity have been described. Future directions for achieving increased hydrogen storage and process scale up have been outlined. Despite few limitations in storing hydrogen in the form of clathrates, this domain receives prominent attention due to more environmental-friendly method of synthesis, easy recovery of molecular hydrogen with minimum energy requirement, and improved safety of the process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Clathrates; Gas hydrates; Hydrogen hydrates; Hydrogen storage; Promoters; Storage capacity

Quasi-molecular hydrogen storage capacity of graphene quantum dots: A dispersion corrected DFT study - Khadilkar, Pranav; Samudre, Nikhil S.; Krishnamurty, Sailaja (Journal of Energy Storage, 2024)
Efficient storage of hydrogen, green fuel with the highest energy density, remains a pressing challenge. Among the several materials investigated for their potential hydrogen storage, 2D materials, like graphene, have advantages such as mechanical strength and large surface area but fail to store hydrogen reversibly. In this context, the present computational experiment demonstrates the potential of Graphene Quantum Dots (GQDs) with 24, 40 and 42 carbon atoms for their hydrogen storage capacity in quasi-molecular mode. Factors such as edge terminations, heteroatom doping, and anchoring of metal atoms are evaluated as a function of their storage capacity. The study clearly demonstrates an enhanced storage capacity of quantum dots, particularly, when a single Ti adatom is anchored on a 24 carbon atom GQD with a storage weight % of 2.24 % w/w. The storage weight % is further noted to increase as a function of the number of Ti atoms anchored on the GQD with the highest hydrogen storage weight % of 6.1 % w/w. Importantly, the adsorption of hydrogen molecule on the Ti atom is through a quasi-molecular mode and is driven by Kubas interaction. This type of interactions makes GQDs as viable storage materials at room temperature. Secondly, the work demonstrates that GQDs offer higher storage capacities of hydrogen molecules as compared to their 2D counterparts viz., graphene sheets, making them attractive candidates to be explored experimentally.
Keywords: Density functional theory; graphene quantum dots; Hydrogen storage; Kubas interaction; Quasi -molecular adsorption; Ti adatom

Retrieval augmented generation for building datasets from scientific literature - Maharana, Piyush Ranjan; Verma, Ashwini; Joshi, Kavita (Journal of Physics-Materials, 2025)
In this work, we show that employing retrieval augmented generation (RAG) with a large language model (LLM) enables us to extract accurate data from scientific literature and construct datasets. The rapid growth in publications necessitates the automation of extraction of structured data as it is crucial for training machine learning(ML) models. The pipeline developed is simple and can be adjusted accordingly with natural language as input. Quantization enables us to run LLMs on consumer hardware and remove the reliance on closed-source models. Both Llama3-8B and Gemma2-9B with RAG give structured output consistently and with high accuracy as compared to direct prompting. Using the newly developed protocol, we created a data set of metal hydrides for solid-state hydrogen storage from paper abstracts. The accuracy of the generated dataset was >88% in the cases tested. Further, we demonstrate that the generated dataset is ready-to-use for ML models by testing it with HYST to predict the H(2)wt% at a given temperature. Thus, we demonstrate a pipeline to create datasets from scientific literature at minimal computational cost and high accuracy.
Keywords: dataset building; Hydrogen storage; LLM; materials; RAG

Pathfinder: adaptive learning for hydrogen storage material optimizationa - Verma, Ashwini; Joshi, Kavita (International Journal of Hydrogen Energy, 2026)
Progress in solid-state hydrogen storage is constrained by time-consuming experiments and scarce high-quality data, limiting effective use of machine learning. To address this, we present an adaptive learning (AL) framework that integrates uncertainty quantification within a closed-loop workflow for targeted material optimization. Unlike static models, it adaptively selects compositions to maximize information gain and improve predictive performance. As a proof of concept, we predict pressure-composition-temperature (PCT) isotherms of Mg-Ni-La systems using literature data for Mg-Ni. The framework identifies informative compositions across Mg fractions (92%-4%) and temperatures (300-633 K), demonstrating effective exploration of the chemical space. For ten unseen compositions evaluated sequentially, accuracy reaches 80% within five cycles, with predictions aligning well with experiments. This establishes a family-specific predictive tool for Mg-Ni-based systems, while the underlying AL framework is broadly applicable to other chemical families with modest initial experimental datasets.
Keywords: Adaptive learning; Hydrogen storage; Metal hydrides; PCT isotherms

What drives property prediction for solid-state hydrogen storage? data or smart features? - Verma, Ashwini; Joshi, Kavita (International Journal of Hydrogen Energy, 2026)
Metal hydrides play a pivotal role in a wide range of applications, including hydrogen storage, compression, heat management, and catalysis, making them a central focus of interdisciplinary research spanning chemistry, materials science, and engineering. The performance of the metal hydride-based systems is strongly governed by the thermodynamics of metal-hydrogen interactions. Among key thermodynamic properties, the equilibrium plateau pressure (P-eq) is particularly critical, as it defines operating conditions for hydrogen absorption and desorption. Traditionally, determining P-eq requires extensive experimental measurements, which limits the pace of materials discovery. On the other hand, predicting it through ML-based models is constrained by the availability of limited data. In this work, we demonstrate that smart features can be a way to overcome this limitation. EquiP, an ML model trained to predict ln(P-eq) as a function of temperature, generates Van't Hoff plots (P-eq vs. 1/T), enabling rapid determination of enthalpy and entropy of hydride formation. We demonstrate that incorporating structural descriptors derived from X-ray diffraction (XRD) data improves the performance of the model, particularly with sparse training datasets. A model trained using only compositional descriptors yields a validation mean absolute error (MAE) of 0.21 bar, whereas incorporating XRD features reduces the MAE substantially to 0.07 bar. This work demonstrates that with limited data, intelligent feature design grounded in domain knowledge is the key to improving predictions of complex material properties.
Keywords: Experimental data; Feature engineering; Hydrogen storage; machine learning; Metal hydrides; Property prediction